1990
DOI: 10.2527/1990.6871889x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of crossbred progeny of polled Hereford sires divergently selected for yearling weight and maternal ability.

Abstract: Polled Hereford sires (n = 47) were divergently selected on published yearling weight (YW) and maternal (MAT) expected progeny differences (EPD) and mated to grade Angus cows to produce 457 calves in five spring calf crops. Sires selected for high and low YW differed by an average of 6.3 kg in YW EPD and those selected for high and low MAT differed by an average of 4.0 kg in MAT EPD based on 1989 EPD values. Calves by high-YW sires were heavier at birth (2.2 kg; P less than .10) and weaning (7.5 kg; P less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Given this assumption, if milk has a genetic correlation of 1 with 12-h milk production, heritability of 12-h production is a. For sires in this study, a , , , was obtained transforming Beef Improvement Federation (BIF) accuracy (Benyshek et al, 19881, reported in the Polled Hereford Sire Summary, into the correla tion between the predicted (EPD,", and the true breeding value of the individual (G,") (Mahrt et al, 1990) and averaged .98. The observed correlation of .26 would thus equate to an estimate of l-& of .28, which is reasonably consistent with previous reports of heritabilities of milk production in dairy cows Maijala and Hanna, 1974;Wade and Van Vleck, 1989).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Given this assumption, if milk has a genetic correlation of 1 with 12-h milk production, heritability of 12-h production is a. For sires in this study, a , , , was obtained transforming Beef Improvement Federation (BIF) accuracy (Benyshek et al, 19881, reported in the Polled Hereford Sire Summary, into the correla tion between the predicted (EPD,", and the true breeding value of the individual (G,") (Mahrt et al, 1990) and averaged .98. The observed correlation of .26 would thus equate to an estimate of l-& of .28, which is reasonably consistent with previous reports of heritabilities of milk production in dairy cows Maijala and Hanna, 1974;Wade and Van Vleck, 1989).…”
Section: Resultsmentioning
confidence: 98%
“…The pooled within-group SD in YW EPD, MAT EPD, and MILK EPD were 4.1, 3.4, and 2.9, respectively, indicating that significant differences among sires groups in EPD were achieved. Details of sire sampling and general cow-calf management were given by Mahrt et al (1990). At milking, cows were 2 to 6 yr old and had calved between February 13 and April 24.…”
Section: Methodsmentioning
confidence: 99%
“…Direct selection using EPD has been demonstrated to improve growth traits (Hough et al, 1985;Mahrt et al, 1990), birth weight (Arnold et al, 1990;Lykins et al, 2000), and carcass traits (Gwartney et al, 1996;Vieselmeyer et al, 1996;Bertrand et al, 1997) in beef cattle. Traditional carcass evaluation programs have utilized carcass data produced from a structured sire progeny testing program.…”
Section: Analyses Using Ultrasound Expected Progeny Differencementioning
confidence: 99%
“…BERTRAND et al (1985), analisando dados da raça Hereford, nos quais o número de touros era relativamente grande (de 87 a 373), obtiveram componentes de variância da interação touro x rebanho igual ou mesmo maior que o componente entre touros. De qualquer forma, a importância da interação touro x rebanho tem sido vista com reserva à luz da sua menor importância quando observada em experimentos delineados (MAHRT et al, 1990; NOTTER e CUNDIFF, 1991) e em análises de dados de campo usando diferente metodologia (GARRICK et al, 1989). Entretanto, NOTTER et al (1992), na raça Angus, na Austrália, usando o método de máxima verossimilhança restrita (REML), obtiveram estimativas significativas para o componente de variância da interação touro x rebanho no peso à desmama.…”
Section: Introductionunclassified